Managing with Asperger Syndrome - Johnson, Malcolm, 1967- (Jessica Kingsley, 2005)
This insider account provides much-needed information about a subject of increasing interest: people with Asperger Syndrome (AS) working in management positions. Johnson draws on his personal experiences to explain how elements such as the working environment, managing staff, group dynamics and office politics can have a profound influence on work performance. He provides useful examples and guidance on adapting to the workplace and coping with the pressures and demands of professional roles. Full of practical advice, this book will be essential reading for anyone with AS in employment as well.